E-Commerce Via Whatsapp: Analysis of the "One-Click Virtual Mall" Developed by Migrants in Chile - Margarit-Segura, D (UNIV NACL COLOMBIA, 2022)
The article problematises the digitalisation of small-scale sales, based on mobility restrictions in the face of the expansion of COVID-19 in the city of Santiago. The case studied is the "Mall virtual a un click", an initiative managed by organisations of Colombian migrant entrepreneurs in Chile The proposal used mass groups on WhatsApp as a digital showcase that allowed them to continue selling, despite the restrictions that prevented them from continuing to develop sales at entrepreneurial fairs. The research recorded, through digital ethnography, the interactions of the group of entrepreneurs between May and September 2021 and complemented the analysis with an online survey and in-depth interviews. The study analysed mobilities and identified a continuum between the presence in the online space for the promotion of products and the place in the city from which marketing is generated, specifically from the home as the starting point of the process. Thus, the digital sale studied evidences the reproduction of socio-spatial inequalities, beyond the unlimited reach that e-commerce could offer to customers.